Rivet die design and optimization for electromagnetic riveting of aluminium alloy joints. Issue 5 (4th May 2021) - Qin, Yangfan; Jiang, Hao; Cong, Yanjun; Li, Guangyao; Qi, Lin; Cui, Junjia
Abstract : A parameter optimization procedure for designing rivet dies is presented to improve the joining quality of an electromagnetic riveted joint. The optimal Latin hypercube sampling technique, radial basis function neural network model and Hooke–Jeeves algorithm were used to construct the optimization model. The results indicated that the rivet die angle was more sensitive to the expansion of the rivet shaft compared to the height. The optimal angle and height of the rivet die were found to be 20° and 2.68 mm, respectively. Relative to a joint with regular rivet die, the average relative interference of the optimized joint increased from 0.35% to 3.50%. This is because the designed rivet die restricted the deformation of the formed head and led to greater expansion of the rivet shaft in the restricted upsetting stage. The shear and pull-out strengths of the joint after optimization were increased by 5.20% and 11.41%, respectively.